(untitled) (Bombay Hospital Journal, 2024)
Intestinal obstruction during pregnancy is a rare condition, which is associated with significant risk for feto-maternal morbidity and mortality. Often there is a delay in diagnosis due to lack of specific symptoms. A 34 years primigravida at 27 weeks of gestation presented with small bowel obstruction which was confirmed on CT scan. She underwent a laparotomy which revealed an adhesive band from omentum to the degenerating fibroid obstructing the ileum. Prompt diagnosis and timely surgical intervention avoids increased morbidity and mortality.